Bioethical perspectives of the everyday living for people with dementia: from decision autonomy to caring for the future - Lygnos, Dimitrios; Rethymniotaki, Eleni (Bioethica, 2023)
Dementia poses a challenge to individuals' good judgment and autonomy, while undermining their quality of life. Ethical issues are faced by people with dementia themselves, their carers and health care providers on a daily basis. Such aspects span a wide spectrum, including not only the serious issues of end-of-life decisions, but also simple everyday problems such as driving. The interdisciplinary approach to bioethical issues highlights dementia as an important and multifaceted social phenomenon. Changes in cognitive abilities and daily activities affect interpersonal interactions and family relationships. Patients, their social environment, and clinicians are called upon in a new context to work together towards decision making about the diagnostic process, daily living, care coordination, advance planning, or end-of-life interventions. The close relations between ethics and law are timeless, making it necessary to study ethical issues alongside legislation.